Flavonoid HPLC fingerprints of wild Vigna species - Lattanzio, V.; Cardinali, A.; Linsalata, V.; Perrino, P.; Ng, N. (1997)
Thirty-two wild species and varieties of Vigna of different origin were screened for their flavotioid content. The compounds detected were utilizcd to assess both interand intraspecific relationships. Flavonoid HPLC fingerprints support evidence for the existence of different flavonoid chemotypes. which may reflect differences in geographic origin. As far as interspecific relationships ;irc concerned, species belonging lo sections Vigna, Plectotropis, and Ceratotropis do not show flavonoid glycosides in common with cultivated lines of Wgiui. By contrast, some relationships have been found between cultivated lines and wild species of section Ctitiang. A greater variability in llavonoid aglyconc class and glycosylalion pattern has been observed in cuitivars of V. unguiculata (L.) Walp.. compared to the wild species. The taxonomic and ecological significance of these findings is discussed. Finally, the existence of a positive relationship between resistance/susceptibility characteristics against aphids and qualitative and/or quantitative flavonoid content is also discussed.